(untitled) (Medical Forum Monthly, 2024)
Objectives: This study was carried out to evaluated the epidemiological aspects of patients presenting with eclampsia in the Shaikh Zaid Women Hospital, Larkana. Study Design: Descriptive retrospective observational study Place and Duration of Study: This study was carried out in the Department of Obstetric & Gynaecology SZWH, CMC & SMBBMU, Larkana from Jan 2012 to Dec 2013. Materials and Methods: All the patient admitted in eclmpasia were included in the study. All the patients were managing according to basic protocol for eclampsia. The data were compiled for frequency distribution of eclmapsia according to gage, parity, socioeconomic status of the patients and seasonal variation. Pregnant patient with other convulsive disorder and more than 7 days post-partum were excluded. Results: In the duration of study of 24 months 50.8% cases of Eclampsia occur in Summer, 25% in Autumn, 12.9% in Winter and 11.2% in Spring Season. During this period of 24 months > 10977 patients were admitted in SZWH, Larkana out of them 108( 0.98%)were cases of eclampsia. Conclusion: Pre eclampsia and eclampsia are major obstructed complication with unclear etiologies. Understanding the exist association with different weather patterns may help us in understanding what factors may be involved in triggering these events.